An Assessment of Burnout among Graduate Students in Health Professional Programs - Hansen, Svanhild B; Virden, Thomas (International journal for the scholarship of teaching and learning, 2022)
Objective: To measure the level of burnout among graduate students in health professional programs. A comparative analysis was used to explore differences in burnout scores among the participating programs. Methods: The Copenhagen Burnout Inventory (CBI) was distributed to students at two Universities with a focus on health professional educations. We assessed for demographics such as gender differences, and added an additional scale aimed at measuring school-related burnout. Results: Burnout and program dissatisfaction were positively correlated. Students in their third year reported the highest burnout scores, with the pharmacy program reporting the highest scores of burnout across all the programs participating. Women reported higher levels of personal burnout, whereas men reported higher levels of client related burnout. Conclusion: Burnout is prevalent among graduate students in health profession programs during the course of their education; interestingly, this appears to be more impactful among pharmacy students. Implications and suggestions for mitigating this impact are discussed.